2010
DOI: 10.1673/031.010.0601
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sleeve Nets to Improve Survival of the Boisduval Silkworm,Anaphe panda, in the Kakamega Forest of Western Kenya

Abstract: Prospects for development of a wild silk industry in Africa would be improved if silkworm survival during mass production could be improved. A study on the survival of the Boisduval silkworm, Anaphe panda (Boisduval) (Lepidoptera: Thaumetopoeidae) was conducted with and without protection by net sleeves in two different forest habitats (natural and modified) in the Kakamega forest of western Kenya. Overall, cohort survival was significantly higher (P < 0.001) in the natural than in the modified forest, but lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…panda silk provides excellent opportunities for African countries. Mbahin et al [43], who studied their occurrence on the tree B . micrantha , recommended the management of indigenous forests in a sustainable way in Africa as the occurrence of wild silk moths is declining due to deforestation and overconsumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…panda silk provides excellent opportunities for African countries. Mbahin et al [43], who studied their occurrence on the tree B . micrantha , recommended the management of indigenous forests in a sustainable way in Africa as the occurrence of wild silk moths is declining due to deforestation and overconsumption.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has been suggested that these resources should be better exploited in a sustainable manner as they are currently threatened by deforestation and overexploitation [75]. The same author suggests ways for a better exploitation [43]. In Madagascar, wild silks are very expensive and they are used in burial ceremonies.…”
Section: Discussionmentioning
confidence: 99%
“…The spores and crystals produced by the B. thuringiensis strains were recovered using a bacteriological loop and suspended in 1 mL of sterile water. The spore-crystal complex was treated with 1 mM protease inhibitor PMSF (phenylmethylsulfonyl fluoride) to avoid protein degradation [ 17 ]. The total protein was quantified by the Bradford technique [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“… 2 Important species used in the production of Anaphe silk include A. infracta (Walsingham), A. venata (Butler), A. panda (Boisduval), A. reticulata (Walker), A. carteri (Walsingham), A. moloneyi (Druce), and A. ambrizia (Butler). 3 Anaphe panda has significant potential in many African countries as a source of income for rural communities and conservation of biodiversity through wild silk production because it produces a huge cocoon nest that is communally weaved by 20–200 silkworm larvae. 4 , 5 Larvae of Anaphe spp.…”
Section: Introductionmentioning
confidence: 99%